Współczesne wyzwania w zarządzaniu projektami informatycznymi - Szyjewski, Zdzisław (Contemporary Challenges in IT Project Management, 2005)
IT project management is a profession that still develops. Growing complexity of the projects aims, causes also rise of requirements given to IT project manager. Problems that appear during implementation are not only connected with the IT learning, but also concern other areas of knowledge. Growth in greatness and complication of the nowadays projects and market competition are the main reason to continue improvement of the manager skills all the time.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 305-313